Analisis Pengaruh Tujuan Pembelajaran yang Jelas Terhadap Ketercapaian Pembelajaran Biologi Siswa SMA - Dini Nurrahmawati (Universitas Nusantara PGRI Kediri, 2024)
Learning objectives are defined as statements that specify the goals to be achieved in the learning process. The learning objectives of biology in schools are mainly centered on improving students' ability to think critically, creatively, and analytically as well as increasing their understanding of the benefits of biology in everyday life. This research takes a qualitative approach by using the literature study method as its main foundation. The main focus of the research is to explore an in-depth understanding of the relationship between learning objectives and their achievement for biology learning in high school. The data analysis process is carried out systematically to classify information, identify, and synthesize the findings obtained from the literature studied.The purpose of learning design is to improve the quality and effectiveness of the teaching and learning process. This can be achieved by selecting, determining and developing the most appropriate and optimal learning methods based on the needs and characteristics of students, the learning objectives to be achieved and the resources available. A good learning design will ensure that the learning process runs smoothly and achieves the desired results. Clear learning objectives have a significant influence on the achievement of biology learning in high school students. The formulation of clear biology learning objectives and teachers' efforts to realize them are important factors in improving the quality and achievement of biology learning in high school students.